Global Point Prevalence Survey of Squamous cell carcinoma in Ten Teaching Hospitals in Iraq - AL-Kafaji, Raid Razak Ali (Technium BioChemMed, 2024)
The type of cancer stages is one of the most important aspects of squamous cell carcinoma. In order to create an appropriate and successful treatment programme in Iraq, the purpose of this study is to evaluate the squamous cell carcinoma patterns in Iraqi hospitals through a survey and identify quality indicators. Within the 10 primary teaching hospitals in Iraq, a point prevalence study was conducted. Every patient admitted to a hospital was included in the study. Comprehensive data on patients who underwent treatment for squamous cell carcinoma were sought after by the study. Among the 649 included patients, comprised 347 of male and 302 of female. A highly significant difference is between the whole sites tumor types of the squamous cell carcinoma patterns at P-value<0.05 except in lower lip, dorsal surface and other. The patients’ mean age was 55.85 years, with males affected at a rate ten years older than females (p<0.05). The current study identified a number of quality indicators that require improvement, including as Iraqi hospitals’ overprescription of squamous cell carcinoma patterns. Data from the global point prevalence study of squamous cell carcinoma will assist Iraq’s health officials in creating an action plan aimed at enhancing the appropriate treatment of squamous cell carcinoma.